Insulin-Mediated Changes in Tau Hyperphosphorylation and Autophagy in a Drosophila Model of Tauopathy and Neuroblastoma Cells - Chatterjee, Shreyasi; Ambegaokar, Suren. S.; Jackson, George R.; Mudher, Amritpal (Frontiers in Neuroscience, 2019)
Almost 50 million people in the world are affected by dementia; the most prevalent form of which is Alzheimer’s disease (AD). Although aging is considered to be the main risk factor for AD, growing evidence from epidemiological studies suggests that Type 2 diabetes (T2DM) increases the risk of dementia including AD. Defective brain insulin signaling has been suggested as an early event in AD and other tauopathies but the mechanisms that link these diseases are largely unknown. Tau hyperphosphorylation is a hallmark of neurofibrillary pathology and insulin resistance increases the number of neuritic plaques particularly in AD. Utilizing a combination of our Drosophila models of tauopathy (expressing the 2N4R-Tau) and neuroblastoma cells, we have attempted to decipher the pathways downstream of the insulin signaling cascade that lead to tau hyperphosphorylation, aggregation and autophagic defects. Using cell-based, genetic and biochemical approaches we have demonstrated that tau phosphorylation at AT8 and PHF1 residues is enhanced in an insulin-resistant environment. We also show that insulin-induced changes in total and phospho-tau are mediated by the crosstalk of AKT, GSK-3β and ERK located downstream of the insulin receptor pathway. Finally, we demonstrate a significant change in the levels of the key proteins in the mTOR/autophagy pathway, implying an increased impairment of aggregated protein clearance in our transgenic Drosophila models and cultured neuroblastoma cells.